Uncertainty and Monetary Policy during the Great Recession - Giovanni Pellegrino; Efrem Castelnuovo; Giovanni Caggiano (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We employ a nonlinear VAR framework and a state-of-the-art identification strategy to document the large response of real activity to a financial uncertainty shock during and in the aftermath of the great recession. We replicate this evidence with an estimated DSGE framework featuring a concept of uncertainty comparable to that in our VAR. We then use the estimated framework to quantify the output loss due to the large uncertainty shock that materialized in 2008Q3. We find such a shock to be able to explain about 60% of the output loss in the 2008-2014 period. The same estimated model unveils the role successfully played by the Federal Reserve in limiting the output loss that would otherwise have occurred had monetary policy been conducted as in normal times. Finally, we show that the rule estimated during the great recession is able to deliver an economic outcome closer to the flexible price one than the rule describing the Federal Reserve's conduct in normal times.
Keywords: C22; E32; E52; 330; uncertainty shock; nonlinear IVAR; nonlinear DSGE framework; minimum-distance estimation; great recession